2017
DOI: 10.1136/bmjopen-2017-015997
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of funding of clinical trials: cross-sectional survey and proposed guidance

Abstract: ObjectivesTo provide a detailed and current characterisation of funding of a representative sample clinical trials. We also aimed to develop guidance for standardised reporting of funding information.MethodsWe addressed the extent to which clinical trials published in 2015 in any of the 119 Core Clinical Journals included a statement on the funding source (eg, whether a not-for-profit organisation was supported by a private-for-profit organisation), type of funding, amount and role of funder. We used a stepwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 55 publications
1
35
4
Order By: Relevance
“…HPSR papers do not compare favourably with clinical papers in terms of the reporting of funding. Recently, we found that 89% of clinical trial reports published in 2015 included funding statements [ 16 ], a percentage substantively higher than the 69% found for HPSR papers herein. In addition, we found that 50% of the clinical trials described as funded reported on the role of funders, a much higher percentage than the 11% found for HPSR papers herein [ 16 ].…”
Section: Discussioncontrasting
confidence: 60%
“…HPSR papers do not compare favourably with clinical papers in terms of the reporting of funding. Recently, we found that 89% of clinical trial reports published in 2015 included funding statements [ 16 ], a percentage substantively higher than the 69% found for HPSR papers herein. In addition, we found that 50% of the clinical trials described as funded reported on the role of funders, a much higher percentage than the 11% found for HPSR papers herein [ 16 ].…”
Section: Discussioncontrasting
confidence: 60%
“…However, it often remains unclear in published papers whether industry sponsors have exerted a catalytic, modest, or no influence on the paper. CONSORT requires reporting of funding sources and conflicts of interest [ 14 ], but reporting remains suboptimal [ 15 ]. There is even less transparency on industry-led ghostwriting of the published reports [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sponsors are the only ones that have full access to the study information. Although papers are presented and authored by independent investigators, statistical analyses are performed by Pharma personnel and manuscripts are prepared by medical writers 26 .…”
Section: Lack Of Transparency In the Planning And Execution Of The Stmentioning
confidence: 99%